CALR, JAK2 and MPL mutation status in Argentinean patients with BCR-ABL1- negative myeloproliferative neoplasms - Ojeda, Mara Jorgelina (2018)
Objectives: To establish the frequency of JAK2, MPL and CALR mutations in Argentinean patients with BCR-ABL1-negative myeloproliferative neoplasms (MPN) and to compare their clinical and haematological features. Methods: Mutations of JAK2V617F, JAK2 exon 12, MPL W515L/K and CALR were analysed in 439 Argentinean patients with BCR-ABL1-negative MPN, including 176 polycythemia vera (PV), 214 essential thrombocythemia (ET) and 49 primary myelofibrosis (PMF). Results: In 94.9% of PV, 85.5% ET and 85.2% PMF, we found mutations in JAK2, MPL or CALR. 74.9% carried JAK2V617F, 12.3% CALR mutations, 2.1% MPL mutations and 10.7% were triple negative. In ET, nine types of CALR mutations were identified, four of which were novel. PMF patients were limited to types 1 and 2, type 2 being more frequent. Discussion: In ET, patients with CALR mutation were younger and had higher platelet counts than those with JAK2V617F and triple negative. In addition, JAK2V617F patients had high leucocyte and haemoglobin values compared with CALR-mutated and triple-negative patients. In PMF, patients with mutant CALR were associated with higher platelet counts. Conclusion: Our study underscores the importance of JAK2, MPL and CALR genotyping for accurate diagnosis of patients with BCR-ABL1-negative MPN.